PO240 Using routinely recorded data in a clinical trial. (1st December 2017) - Powell, Graham; Bonnett, Laura; Tudur-Smith, Catrin; Hughes, Dyfrig; Williamson, Paula; Marson, Tony
Abstract : There are a number of clinical and non-clinical administrative datasets that routinely record information on individuals in the UK. Access for secondary uses such as clinical research is permitted when health and social care benefit can be demonstrated. Clinical sources of data are commonly accessed to provide data for retrospective observational and record-linkage studies and provide a valid dataset for this purpose. Routinely recorded data may also present advantages to prospective clinical research such as randomised controlled trials (RCTs). The majority of RCTs incur health service costs as clinicians assess participants, record outcomes and complete Case Report Forms – hence using routinely recorded data may provide an efficient alternative method for data collection in addition to reducing the burden on participants. Furthermore, data from non-clinical routine sources may inform outcomes beyond the standard RCT assessments of clinical efficacy and effectiveness. However, limitations with accuracy of coding, confidentiality, ownership and access have previously been identified as significant barriers. This study has assessed the feasibility of accessing clinical and non-clinical routinely recorded data during a RCT assessing treatments for newly diagnosed epilepsy and will assess the agreement and additional benefits of routinely recorded data compared to data collected using standard prospective methods.